Inter-Jurisdictional Competition for Firms: Jobs as Vehicles for Redistribution - Robin Boadway; Katherine Cuff; Nicolas Marceau (Queen's University, Department of Economics, 1999)
Regions inhabited with an immobile population of disabled and able individuals compete to attract mobile firms that provide jobs. The redistributive goal of regional governments is to support the disabled, who cannot work. Able individuals may work, be involuntary unemployed because of frictions in the labour market, or choose to be voluntary unemployed. Labour force participation decisions depend on regional redistributive policies. Both the size of workforce and tax on firms affect profits and therefore, firms' location decisions. Allowing regions to engage in tax competition may be efficient. If regions cannot tax firms, they compete by implementing inefficient redistributive policies.
Keywords: H2; H7; J6; 330; Inter-Jurisdictional Competition; Redistributive Policies; Unemployment